Unite Or Die: How Thirteen States Became a Nation - Jacqueline Jules (Charlesbridge Publishing, 2009)
Using the conceit of a school play, Unite or Die traces the challenges, conflicts, and compromises that shaped the living document we call the United States Constitution. This accessible introduction to the drafting of the Constitution features exuberant illustrations and an engaging style suitable for readers theater.
Grade - 6
Keywords: PY-UOI-How We Organise Ourselves